2012
DOI: 10.1167/iovs.11-9228
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asymptomatic and Symptomatic Meibomian Gland Dysfunction in the General Population of Spain

Abstract: PURPOSE.To describe epidemiologic characteristics of asymptomatic and symptomatic meibomian gland dysfunction (MGD) in a general adult population in northwestern Spain. METHODS.A total of 1155 subjects aged 40 years and older were selected by an age-stratified random sample procedure in O Salnés, Spain. A standardized symptoms questionnaire was administered and a comprehensive ophthalmic evaluation, which included ocular surface tests, was carried out. Absent, viscous, or waxy white secretion upon digital expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
140
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 34 publications
10
140
3
5
Order By: Relevance
“…This is supported by previous work that examined the relationship between Schirmer's score and symptoms, 27,28 and by a recent article that showed that many patients with objective meibomian gland dysfunction were asymptomatic. 29 This finding is problematic given that the main source of morbidity in DES is the symptomatology. DES symptoms, which include irritation, foreign body sensation, and pain, interfere with the ability to work and carry out daily functions.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous work that examined the relationship between Schirmer's score and symptoms, 27,28 and by a recent article that showed that many patients with objective meibomian gland dysfunction were asymptomatic. 29 This finding is problematic given that the main source of morbidity in DES is the symptomatology. DES symptoms, which include irritation, foreign body sensation, and pain, interfere with the ability to work and carry out daily functions.…”
Section: Discussionmentioning
confidence: 99%
“…29 On the other hand, patients may experience symptoms of dry eye in the absence of any clinical signs. 38 The disagreement between symptoms and signs may be an additional support for the use of TFO measurements to determine the severity of dry eye. Neves Mendes et al 39 conducted a case-controlled study to evaluate ocular surface changes in posttrabeculectomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio realizado España con una población mayor de 40 años, se encontró una prevalencia del 11%; lo que viene a ser en términos numéricos, cinco millones de españoles (4). A nivel mundial los datos de prevalencia no están del todo claros, dependen de la definición de ojo seco usada, de la distribución geográfica donde se evalúe y del rango de edad de la población analizada (4,6).…”
Section: Introductionunclassified
“…Los datos de prevalencia son preocupantes, con el agravante de que se estima que existen treinta y tres millones de adultos sin diagnosticar en el mundo (4). En el ámbito de la salud pública es una patología incapacitante, con un impacto significativo en cuanto a calidad de vida se refiere.…”
Section: Introductionunclassified